Characteristics and quality of clinical practice guidelines for depression in adults: a scoping review - Zafra-Tanaka, Jessica Hanae (2019)
Clinical Practice Guidelines (CPGs) should follow an adequate methodology using an evidence-based approach in order to provide reliable recommendations. However, little is known regarding the quality of CPGs for Depression, which precludes its adequate use by stakeholders and mental health professionals. Thus, the aim of this study was to conduct a scoping review to describe the characteristics and quality of CPGs for Depression in adults.